PERANCANGAN BUKU INTERAKTIF CARA MEMAINKAN WAYANG GOLEK UNTUK ANAK USIA 6 – 9 TAHUN DI KAMPUNG SENI JELEKONG - Suhendi, Fadia Ramdhilla; Nastiti, Nisa Eka; Alifaprilina Supriadi, Olivine (Telkom University, 2024)
Jelekong Art and Culture Village is one of the places to preserve wayang golek in Bandung Regency. Padepokan GiriHarja is a wayang golek art group in Jelekong. There is one puppeteer named Adhi Kontea Kosasih Sunarya Putu GiriHarja 2who actively opens puppetry training for children. According to Adhi, not many children can play wayang golek because of several factors. The main factor is the lack of education on how to play wayang golek. By creating educational media that is suitable for children to read. The purpose of designing this final project is to be able to find out how to make educational media on how to play wayang golek and educate children aged 6-9 years to play wayang golek. The research data was collected through direct observation to Jelekong Art and Culture Village, interviews, documentation, and literature studies with qualitative research methods. Keywords: wayang golek, how to play, Jelekong, children, educational media.